2023
DOI: 10.1186/s12889-023-15079-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 prevention at institutions of higher education, United States, 2020–2021: implementation of nonpharmaceutical interventions

Abstract: Background In early 2020, following the start of the coronavirus disease 2019 (COVID-19) pandemic, institutions of higher education (IHEs) across the United States rapidly pivoted to online learning to reduce the risk of on-campus virus transmission. We explored IHEs’ use of this and other nonpharmaceutical interventions (NPIs) during the subsequent pandemic-affected academic year 20202021. Methods From December 2020 to June 2021, we collected publ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It may be, therefore, that university campuses are fortunate in experiencing no epidemic with only limited controls. A recent study found that while most higher education institutions in the United States enforced relatively low-cost non-pharmaceutical interventions against COVID-19 such as mandating mask wearing indoors, only 20% of those sampled instituted all of the interventions recommended by the Centers for Disease Control and Prevention, including on-campus testing and restrictions on mixing [24]. Our work would suggest that, while undoubtedly costly and with important considerations for wellbeing, the more measures implemented the better for disease control.…”
Section: Discussionmentioning
confidence: 99%
“…It may be, therefore, that university campuses are fortunate in experiencing no epidemic with only limited controls. A recent study found that while most higher education institutions in the United States enforced relatively low-cost non-pharmaceutical interventions against COVID-19 such as mandating mask wearing indoors, only 20% of those sampled instituted all of the interventions recommended by the Centers for Disease Control and Prevention, including on-campus testing and restrictions on mixing [24]. Our work would suggest that, while undoubtedly costly and with important considerations for wellbeing, the more measures implemented the better for disease control.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of the COVID-19 pandemic mandated adaptations that disrupted education at all levels and uniquely shaped the academic experience of post-secondary students. Under the guidance of the CDC, colleges and universities across the country implemented several measures to manage the impact of COVID-19 on institutional operations and reduce disruptions to student learning including offering distance learning, adjusting the academic 2 of 16 calendar, limiting student housing, modifying the operations of on-campus facilities and common areas, and enforcing mask-wearing policies [8]. The required adaptations and transitions drastically shaped the higher education experience for all students.…”
Section: Impact Of Covid-19 In Higher Education and The Implications ...mentioning
confidence: 99%
“…With the emergence of the COVID-19 pandemic in March 2020 [1][2][3], many institutions of higher education (IHEs) in the United States proceeded to institute nonpharmaceutical interventions (NPIs) based on the Centers for Disease Control and Prevention recommendations to manage the spread of the SARS-CoV-2. NPIs included using facemasks [4,5], remote learning, physical distancing, significantly limiting mass gatherings, travel restrictions, and implementing distance learning/remote classrooms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Presumably due to the perceived higher risk and concern for contracting SARS-CoV-2 for younger individuals [13]. Although younger individuals and especially college students have an overall lower risk for severe outcomes for SARS-CoV-2, this population could have been a source of transmission during the pandemic [6,14,15].…”
Section: Introductionmentioning
confidence: 99%